SMÅ SKRIDT ELLER ET KÆMPE SPRING: Indfødte folk og de Forenede Nationer - Burger, Julian (Tidsskriftet Antropologi, 1996)
Julian Burger: Small steps or a giant leap: Indigenous people and the United Nations For the first five decades of the existence of the United Nations indigenous people have been absent from the deliberations of the world organization. But over the last fifteen years small but significant changes have occured. The article describes the development of how the indigenous voice „stepwise“, has gained more and more resonance inside the United Nations system. A short history of The Working Group of Indigenous Populations is sketched, elaborating on its most important achievement, the draft declaration on the rights of indigenous peoples. The author outlines the innovating proposals of this unique document, as well as its contested status for some States, specifically conceming the issue of defining the controversial concept of self-determination. Among other activities, initiated by the United Nations on indigenous matters, the article emphazises the studies on historie treaties and indigenous cultural and intellectual property, as well as expert seminars on racism, self-govemment, sustainable development, and land rights. Finally an assesment is made on the possible outeome of the Year and the Decade of Indigenous Peoples, the outeome of which, hopefully, could be a permanent forum for indigenous peoples inside the United Nations system.